Revisão e caracterização da avifauna descrita nos EIA-RIMAs do estado de São Paulo - Frezza, Fernando Henrique Sanches (2022)
The Environmental Impact Assessment (EIA) is an environmental management tool implemented in Brazil based on the National Environmental Policy (Law No. 6,938/81) to assess, predict and mitigate the impacts that will be generated on the environment by the implementation of projects . Articulated with the EIA, the Environmental Impact Studies/Environmental Impact Reports (EIA/RIMAs) aim to assess the feasibility of projects through multidisciplinary analyses, including inventories of the fauna of the affected areas. Birds represent one of the biological groups most impacted by human activities, and about 170 species are classified in some degree of threat of extinction in the state of São Paulo alone. Thus, the objectives of this study were to carry out a comprehensive review of the EIA/RIMAs used for the environmental licensing process in the state of São Paulo from 2000 to 2019 to identify and ecologically classify the bird species that appear in these documents. For this, taxonomic, ecological and morphological characteristics of the species were considered. A total of 662 taxa were recorded in 151 enterprises, the most cited being Pitangus sulphutarus (n=150; 99.34% of enterprises) and Caracara plancus (n=148; 98.01%). Species with medium environmental sensitivity predominated (n=291; 39.27%), with invertebrate feeding preference (n=331; 50%), canopy as foraging stratum (n=92; 13.90%) and forest as habitat. preferred (n=202; 30.51%). Regarding endemic species, six (0.90%) were recorded for the Cerrado domain and 126 (19.03%) for the Atlantic Forest. We found that the many bird species present in the EIA/RIMAs are sensitive to environments modified by human activities, and the EIA-RIMAs are of paramount importance for the detection and protection of these species.